Inovação tecnológica no controle da produção de vinhos no oeste e sudoeste do estado do Paraná - Dezengrini, Elenilton Jairo (2017)
There is a shortage in the wine industry regarding the use of technology and technological problems. This study was divided into three stages. The first step was to analyze the data obtained from the sociodemographic research of wine consumption, using the Theory of Response to the Item (TRI), being divided into six groups: wine purchasing decisions, consumer wine consumption reasons, wine knowledge, Attributes of wine, the style of wine consumption and the risk reduction strategy when buying wine. The research was carried out with 173 employees of the University Center Assis Gurgacz and 127 members of the Center for the Coexistence of the Elderly. The second objective was to obtain information about the production process in wineries located in the west and southeast of the state of Paraná, as well as the technology used in wine production. The third step consisted in creating a software to control the production of the wineries, based on the requirements collected in obtaining the information of the production process. It was found that 66.33% of the wine consumers interviewed had completed higher education, taking into account the minimum schooling, with 79.67% consuming 1 to 4 liters of wine per month and red wine being preferred as the color of wine to 72.67%. The result of the TRI analysis showed a greater tendency for item 2 (flavor), considering that 81% of respondents considered this attribute to be "important" or "very important" when buying wine, followed by 73.34% of respondents who consider the aroma as "important" or "very important". However, only 21.33% of respondents considered advertising "important" or "very important" when buying a wine. None of the wineries visited have software to control wine production and the difficulty factor in production is a shortage of skilled labor for wine processing. The developed software facilitated the stock control, the realization of the cost price, based on the costs of inputs, fixed expenses and variable expenses. Agribusiness has been important for society and this work has contributed to the technological innovation in the productive sector of the wineries, bringing greater assertiveness in the cost of the final product.